A child-friendly school: How the school implements the model - Somariah Fitriani; Istaryatiningtias Istaryatiningtias; Lelly Qodariah (Institute of Advanced Engineering and Science, 2021)
The study was to examine the implementation of child-friendly school (CFS) in a public elementary school. This study employed a single case study method, as Public Elementary School ofRagunan 01 is the unit of research analysis. The school has been declared as a child-friendly school since 2015. The quantitative data generated, however, were only used to see the percentage of the characteristics of CFS model. Thus, the data were gathered through observation, questionnaires and interviews to obtain more comprehensive empirical data. The questionnaire was distributed to all teachers and 15 class coordinators of students’ parents to obtain data about the implementation of CFS. Interviews were conducted with several important multi-stakeholders identified. The results showed that thirteen characteristics of the CFS had been implemented well with a percentage value above 95%. It indicates that this school has been able to realize the CFS model following its principles. Besides, the school has met the requirement of the six essential components of CFS adapted according to Indonesian educational contexts. It indicates that the implementation of CFS is in accordance with the concept of UNICEF but with some differences.